(1 + 7x)*(1 - 7x) [Application of a^2 - b^2 = (a + b)*(a - b)]?

Update:

I could not understand how this question has come in my name: may be due to some wrong operations with the android mobile. I don't know how to delete this question. Request no one need to answer.

6 Answers

Relevance
  • ?
    Lv 7
    4 years ago
    Favorite Answer

    = 1-49x²

    Blame it on quantum fluctuations in electronics. The same reason my wife's iPhone butt dials. [smile]

  • cidyah
    Lv 7
    4 years ago

    1^2 - (7x)^2 = 1 - 49x^2

  • 4 years ago

    (1+7x)(1-7x)= (1)^2 - (7x)^2

    =1 - 49x^2

  • 4 years ago

    1

    Source(s): Ultimate Attraction Guide http://emuy.info/GetEveryGirlEasily/?hLo9
  • How do you think about the answers? You can sign in to vote the answer.
  • 4 years ago

    (1 + 7x)*(1 - 7x)

    = (1)(1) - 7x + 7x + (-7x)(7x)

    = 1 - 49x^2

  • Como
    Lv 7
    4 years ago

    1 - 49 x²

Still have questions? Get your answers by asking now.